An Undergraduate Micro Fabrication Course at the Northern Malaysia University College of Engineering - Uda, Hashim, Prof. Dr.; Zul Azhar, Zahid Jamal, Prof. Dr. (Kolej Universiti Kejuruteraan Utara Malaysia, 2008)
Link to publisher's homepage at http://jere.unimap.edu.my